Studi Bio-Ekologi Rusa di Penangkaran Cinta Pesona Ladangku (CPL) Kuala Bekala Sumatera Utara - Andika Fera Waty Harahap; Pindi Patana; Siti Latifah (Program studi Kehutanan USU, 2015)
Deer are wild animals which have been developed in breeding place because their habitat is corrupted. One of the breeding places in developed is CPL (Cinta Pesona Ladangku) breeding place at Kuala Bekala, North Sumatera. The observed parameter was the correlation between bio-ecological aspect and and the population development of deer. The research used descriptive method. The result of the research showed that the minimum of air temperature in CPL breeding place was 220 C and the maximum of air temperature was 340 C. The population of deer in CPL breeding place has surpassed the capacity of the animal pen. Viewed from some bio-ecological aspects, Bawean deer could not multiply in number in CPL breeding place. The age-structure was an upside down pyramid where the number of fawns was fewer than that of deer. The deer breeding technique needs special attention in order to increase the number of deer population.Keywords : Deer, Breeding place, Bio-ecology, Population.